Co-circulation of Orthobunyaviruses and Rift Valley Fever Virus in Mauritania, 2015 - Cichon, Nicole; Barry, Yahya; Stoek, Franziska; Diambar, Abdellah; Ba, Aliou; Ziegler, Ute; Rissmann, Melanie; Schulz, Jana; Haki, Mohamed L.; Höper, Dirk; Doumbia, Baba A.; Bah, Mohamed Y.; et al. (Frontiers in Microbiology, 2021)
Ngari virus (NRIV) has been mostly detected during concurrent outbreaks of Rift Valley fever virus (RVFV). NRIV is grouped in the genus Orthobunyavirus whithin the Bunyaviridae family and RVFV in the genus Phlebovirus in the family Phenuiviridae. Both are zoonotic arboviruses and can induce hemorrhagic fever displaying the same clinical picture in humans and small ruminants. To investigate if NRIV and its parental viruses, Bunyamwera virus (BUNV) and Batai virus (BATV), played a role during the Mauritanian RVF outbreak in 2015/16, we analysed serum samples of sheep and goats from central and southern regions in Mauritania by quantitative real-time RT-PCR (qRT-PCR), serum neutralization test (SNT) and ELISA. 41 of 458 samples exhibited neutralizing reactivity against NRIV, nine against BATV and three against BUNV. Moreover, complete virus genomes from BUNV could be recovered from two sheep as well as two NRIV isolates from a goat and a sheep. No RVFV-derived viral RNA was detected, but 81 seropositive animals including 22 IgM-positive individuals were found. Of these specimens, 61 samples revealed antibodies against RVFV and at least against one of the three orthobunyaviruses. An indirect ELISA based on NRIV/BATV and BUNV derived Gc protein was established as complement to SNT, which showed high performance regarding NRIV but decreased sensitivity and specificity regarding BATV and BUNV. Moreover, we observed high cross-reactivity among NRIV and BATV serological assays. Taken together, the data indicate the co-circulation of at least BUNV and NRIV in the Mauritanian sheep and goat population.